Malnutrition associated with nutrition impact symptoms and localization of the disease: Results of a multicentric research on oncological nutrition. Issue 3 (June 2019) - de Pinho, N.B.; Martucci, R.B.; Rodrigues, V.D.; D'Almeida, C.A.; Thuler, L.C.S.; Saunders, C.; Jager-Wittenaar, H.; Peres, W.A.F.
Summary: Background & aims: Malnutrition in cancer is an independent factor associated with negative clinical outcomes. The aim was to evaluate the prevalence and independent risk factors for malnutrition in hospitalized cancer patients using the Patient-Generated Subjective Global Assessment (PG-SGA). Methods: We evaluated 4783 cancer patients, aged ≥20 years, in a hospital-based, multicenter, cross-sectional study. Patients were classified as well-nourished (PG-SGA Stage A), moderate/suspected malnutrition (PG-SGA Stage B), or severely malnourished (PG-SGA Stage C), and provided a score to define required nutritional interventions. Multivariate analysis was composed of the odds ratio (OR) estimated by ordinal polytomous logistic regression. Results: 45.3% were classified as Stage B and 11.8% as Stage C. Moreover, 45.3% of the patients presented a need for nutritional intervention. The variables that presented the highest ORs for Stage B or Stage C were: problems with swallowing (OR 2.8, 95% confidence interval (CI) 2.2–3.4, p < 0.001), loss of appetite (OR 1.9, 95% CI 1.6–2.3, p < 0.001), vomiting (OR 1.8, 95% CI 1.5–2.3, p < 0.001), presence of more than 3 nutrition impact symptoms (OR 8.3, 95% CI 5.8–12, p < 0.001), and cancer site: lung (OR 4.6, 95% CI 3.2–6.6, p < 0.001), upper digestive cancer (OR 3.7, 95% CI 2.7–5.2, p < 0.001), and head and neck cancer (OR 3.7, 95% CI 2.7–5.2, p < 0.001). The score for Worksheet 4 on the PG-SGA had a higher association with malnutrition (OR 7.3, 95% CI 6.6–8.2, p < 0.001). Conclusions: Malnutrition is highly prevalent in cancer patients in Brazil, and is associated with nutritional impact symptoms, cancer site and age ≥65 years. Highlights: Malnutrition is highly prevalent in cancer patients in Brazil. The nutrition impact symptoms were independent factors associated with malnutrition. Regard to cancer location, lung, upper digestive and head and neck cancer had a stronger association with malnutrition.